2011
DOI: 10.1002/ijc.26407
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial chemoembolization in the treatment of patients with unresectable cholangiocarcinoma: Results and prognostic factors governing treatment success

Abstract: The aim of the study was to evaluate the effectiveness of transarterial chemoembolization (TACE) with four chemotherapeutic protocols in terms of local tumor control and survival of patients with unresectable cholangiocarcinoma (CCC) and to identify the prognostic factors governing treatment success. In the single-centre study, 115 patients (mean ages 5 60.4 years) with unresectable CCC were repeatedly treated with TACE. In total, 819 chemoembolization sessions were performed in 4 week intervals with a mean of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(89 citation statements)
references
References 49 publications
1
77
0
11
Order By: Relevance
“…148 A similar median survival was demonstrated with mitomycin C (11 months), comparable to the survival of patients with positive LN or positive surgical margins. 149 Treatment of unresectable ICC with doxorubicineluting beads has shown 100% tumor response rate and median survival of 13 months.…”
Section: Hepatic Artery-based Therapiessupporting
confidence: 58%
“…148 A similar median survival was demonstrated with mitomycin C (11 months), comparable to the survival of patients with positive LN or positive surgical margins. 149 Treatment of unresectable ICC with doxorubicineluting beads has shown 100% tumor response rate and median survival of 13 months.…”
Section: Hepatic Artery-based Therapiessupporting
confidence: 58%
“…The median OS was 13 months from initial embolization and no statistically significant differences were observed between regimens (18). A smaller study included 17 patients with unresectable ICC, who underwent a median of two cTACE sessions per patient.…”
Section: A B Cmentioning
confidence: 98%
“…Generally, TACE is tolerated well by the majority of patients without major adverse events. However, abdominal pain, nausea, fever and increase in liver enzymes (limited to 3-4 days without the evidence of sepsis) are frequent transient minor side effects after cTACE procedures and commonly referred to as post-embolization syndrome (16)(17)(18).…”
Section: Ctace-backgroundmentioning
confidence: 99%
“…The overall survival was still less than 1 year (2). Several trials on the effects of transarterial chemoembolization (TACE) also showed a wide range of the relatively short median survival from 12.2-15 months (3)(4)(5). Recently, chemoembolization with drug-eluting beads-TACE was investigated, but the median overall survival was also short -11.7 months (6).…”
Section: Introductionmentioning
confidence: 99%